The regioselective carbonylation and related reactions of functionally substituted alkenes and alkynes catalyzed by rhodium(I) complexes. - Zhou, Jian-Qiang. (University of Ottawa (Canada), 1993)
This thesis comprises research on the regioselective carbonylation and related reactions involving various unsaturated organic substances such as alkenes, alkynes, allylic esters, alcohols and amines, open chain and cyclic $\alpha$,$\beta$-unsaturated esters using cationic, neutral and zwitterionic rhodium(I) complexes as catalysts. New methods for the preparation of valuable functionally substituted derivatives have been developed.
Keywords: Chemistry, Organic.